Monetary Stability under Dual Banking System before Covid-19 Pandemic in Indonesia - Irfan Nurfalah; Ahlis Fatoni (Ekonomi Islam Indonesia, 2023)
The Indonesian monetary authority or the Central Bank of Indonesia has established a policy in accordance with the constitution No. 3 in 2004, the monetary policy taken by Central Bank of Indonesia is the inflation targeting framework (ITF). To achieve this, Central Bank of Indonesia established intermediary policies which are regulating the volume of the money supply, stipulating the minimum reserves banking and regulating credit or financing. From some of these intermediary policies, the authors are interested in researching monetary policy in the dual monetary system in Indonesia, where the instruments used by each monetary system are different, so which system is the most stable and sustains Indonesia's growth and which system is the best to achieve ITF goals. The method used is Autoregressive Distributed Lag (ARDL) with data from 2010-sep 2018. The results show that the instruments used in conventional monetary systems based on interest rates have no influence on economic growth, whereas instruments in the Islamic monetary system have an influence on economic growth.